The Meaning of Artificial Intelligence (AI) Utilization in Business: A Phenomenological Study from the Perspective of Muslim Entrepreneurs in Indonesia - Purnama Putra; Sudana Sudana; Solihah Sari Rahayu (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The development of Artificial Intelligence (AI) has brought significant changes to the business world, including among Muslim entrepreneurs. However, this advancement raises questions about how such technology can be utilized without neglecting Islamic values. This study aims to understand how Muslim entrepreneurs interpret spiritual values, apply Islamic ethics, and perceive the economic and efficiency functions of AI usage.Method: A qualitative method with a phenomenological approach was employed to explore the experiences of Muslim entrepreneurs in Indonesia, selected through purposive sampling. Data were analyzed using NVivo software.Results: The findings reveal that the meaning of AI usage encompasses five core values: tawhid (monotheism), amanah (trustworthiness), sharia compliance, efficiency, and gratitude. The application of Islamic ethics is reflected in honesty, justice, social responsibility, trust, and ihsan (excellence) in the utilization of technology. The interpretation of AI’s economic and efficiency functions is viewed as part of human effort (ikhtiar) to enhance productivity and competitiveness while maintaining spiritual balance and social welfare.Conclusion: The implications of this study highlight the potential for developing AI usage guidelines that align with Islamic ethics, ensuring efficiency and competitiveness while upholding justice and social responsibility.